The Challenge of Establishing World-Class Universities - Salmi, Jamil (World Bank, 2012)
There are many important questions to ask about the widespread push toward world-class status for universities around the world. Why is 'world-class' the standard to which a nation should aspire to build at least a subset of its tertiary education system? Might many countries be better served by developing the most locally relevant system possible, without concern for its relative merits in a global comparison? Is the definition of "world-class" synonymous with "elite Western" and therefore inherently biased against the cultural traditions of tertiary education in non-Western countries? Are only research universities world-class, or can other types of tertiary education institutions (such as teaching universities, polytechnics, community colleges, and open universities) also aspire to be among the best of their kind in an international perspective? To answer these questions, the report starts by constructing an operational definition of a world-class university. It then outlines and analyzes possible strategies and pathways for establishing such universities and identifies the multiple challenges, costs, and risks associated with these approaches. It concludes by examining the implications of this drive for world-class institutions on the tertiary education efforts of the World Bank, offering options and alternative perspectives on how nations can develop the most effective and relevant tertiary education system to meet their specific needs.